Penggunaan Algoritma Greedy untuk Menemukan Jalur ke Rumah Makan Terdekat dari Kampus Melalui Aplikasi Web yang Memperhitungkan Perjalanan Kaki - Firdaus, Muhammad; Firmansyah, Nedi; Utami, Dwi (Jurnal Penelitian Multidisiplin Ilmu, 2025)
The problem of finding the nearest restaurant from campus is often faced by students. This research proposes a web-based solution that implements the greedy algorithm to find the shortest route. The greedy algorithm was chosen because of its ability to make decisions quickly and produce good solutions in many cases. The system will integrate campus geographic data, restaurant locations, as well as road information and other obstacles. The research results are expected to contribute to the development of more efficient location-based navigation applications.